A Traumatic and Infected Left Ventricular Pseudoaneurysm 2 years After the Explantation of a Bridge-to-Recovery Left Ventricular Assist Device - Aziz U; Strachinaru M (International Medical Case Reports Journal, 2025)
Usama Aziz, Mihai Strachinaru Cardiology Department – Erasme Hospital (Université Libre de Bruxelles), Brussels, BelgiumCorrespondence: Usama Aziz, Cardiology Department, Erasme Hospital (Université Libre de Bruxelles), Route de Lennik 808, Brussels, Belgium, 1070, Email Drazizusama@gmail.comAbstract: Left ventricular assist devices (LVADs) have become an important modality of treatment in advanced heart failure, serving sometimes as a bridge to recovery. A subject in his 30s with alcohol-induced dilated cardiomyopathy underwent LVAD implantation following severe cardiac dysfunction. After six years, a sufficient myocardial recovery led to successful LVAD explantation. 2 years post-explant, the patient continued high-risk lifestyle behaviors (like smoking and drinking alcohol) and eventually developed a left thoracic pseudoaneurysm due to a fall with left chest trauma. Surgical repair revealed infection, treated with targeted antibiotics. This case shows a rare echocardiographic presentation and underscores the complexities of LVAD explantation, particularly in patients continuing high-risk lifestyle behaviors. To our knowledge, an infected left ventricular pseudoaneurysm complicating LVAD explantation has not previously been reported. Thus, its management and long-term outcomes could not be assessed using evidence-based guidelines.Keywords: left ventricular assist device, explantation, complication, pseudoaneurysm